Hace1 Influences zebrafish cardiac development via ROS‐dependent mechanisms. Issue 2 (27th October 2017) - Razaghi, Babak; Steele, Shelby L.; Prykhozhij, Sergey V.; Stoyek, Matthew R.; Hill, Jessica A.; Cooper, Matthew D.; McDonald, Lindsay; Lin, William; Daugaard, Mads; Crapoulet, Nicolas; Chacko, Simi; Lewis, Stephen M.; et al.
Abstract : Background: In this study, we reveal a previously undescribed role of the HACE1 (HECT domain and Ankyrin repeat Containing E3 ubiquitin‐protein ligase 1) tumor suppressor protein in normal vertebrate heart development using the zebrafish ( Danio rerio ) model. We examined the link between the cardiac phenotypes associated with hace1 loss of function to the expression of the Rho small family GTPase, rac1, which is a known target of HACE1 and promotes ROS production via its interaction with NADPH oxidase holoenzymes.Results : We demonstrate that loss of hace1 in zebrafish via morpholino knockdown results in cardiac deformities, specifically a looping defect, where the heart is either tubular or "inverted". Whole‐mount in situ hybridization of cardiac markers shows distinct abnormalities in ventricular morphology and atrioventricular valve formation in the hearts of these morphants, as well as increased expression of rac1 . Importantly, this phenotype appears to be directly related to Nox enzyme–dependent ROS production, as both genetic inhibition by nox1 and nox2 morpholinos or pharmacologic rescue using ROS scavenging agents restores normal cardiac structure.Conclusions : Our study demonstrates that HACE1 is critical in the normal development and proper function of the vertebrate heart via a ROS‐dependent mechanism. Developmental Dynamics 247:289–303, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: Our study demonstrates that HACE1 is critical in the normal development and proper function of the heart via a ROS‐dependent mechanism.